Tinjauan Hukum Islam Terhadap Praktik Investasi Syariah di Pasar Modal - Togatorop, Agracecia Ebena; B, Baidhowi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The practice of Islamic investment in the capital market, according to Islamic law, emphasizes adherence to Sharia principles, including prohibitions against riba, gharar, and maisir. In Sharia-compliant capital markets, investment products and transaction mechanisms must meet halal criteria, and profits and losses are regulated through fair profit-sharing principles. Several investment instruments, such as Sharia-compliant stocks, mutual funds, and sukuk, provide opportunities for investors to engage without violating Islamic teachings. The supervision of Sharia investments is carried out by the Sharia Supervisory Board (DPS), the Financial Services Authority (OJK), and Sharia Capital Market Experts (ASPM). However, challenges in implementing Sharia principles remain, including regulatory ambiguity, limited investment instruments, and low Sharia financial literacy. Therefore, it is essential to address these challenges to develop a more inclusive and sustainable Sharia capital market.